Long-term toxicity of the treatment for germ cell-cancer. A review. (January 2018) - Maroto, P.; Anguera, G.; Martin, C.
Abstract: Testicular germ-cell cancer (GCC) is a curable disease. Stage I patients are mostly cured by surgery alone. For those with good prognosis advanced disease, radiotherapy in some patients with stage II Seminoma and chemotherapy for all other patients, are responsible for 95% of long-term survivors. Unfortunately, despite this high level of curability, overall survival has been reported lower for those patients receiving either radiotherapy or chemotherapy versus patients treated by surgery alone. Long-term survivors face a higher incidence of second neoplasms, and a higher risk of cardiovascular disease and metabolic syndrome than expected. Other non-life-threatening toxicities such as ototoxicity, neurotoxicity and fertility problems are common. This paper reviews the potential causes of the higher mortality among long-term survivors of testicular tumors, the incidence of them and some recommendations for the diagnoses and prevention of long-term sequelae in patients with GCC.